2013
DOI: 10.1166/jnn.2013.7244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Performance of 0.3Li2MnO3·0.7LiMO2 (M = Mn, Co, Ni) Cathode Materials for Li-Ion Batteries

Abstract: The Mn0.720Ni0.175Co0.105(OH)2 precursor was co-precipitated by the Couette-Taylor reactor. The 0.3Li2MnO3 x 0.7LiMn0.60Ni0.25Co0.15O2 of the high capacity cathode material for a Li-ion battery was synthesized according to the amount of lithium excess (5-20 mol.%). X-ray diffraction (XRD) and field emission-scanning electron microscopy (FE-SEM) were used to characterize the 0.3Li2MnO3 x 0.7Li-Mn0.60Ni0.25Co0.15O2. Based on the XRD patterns and FE-SEM images, the 5 and 10 mol.% lithium excess samples were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…18 Ryu et al used a Couette-Taylor reactor to co-precipitate 0.3Li 2 MnO 3 • 0.7LiMn 0.60 Ni 0.25 Co 0.15 O 2 and found that 15 mol% excess lithium was necessary to form the desired layered compound. 19 Deng et al found that co-precipitated materials are very sensitive to lithium concentration, and lithium deficiency in the precursor solution can lead to the formation of spinel LiNi 0.5 Mn 1.5 O 4 upon lithiation, which was found to improve the rate capability of the materials upon cycling. 8,13 Since many synthesis methods are used to prepare the layered cathodes, different annealing conditions are applied to the as-synthesized powders, and this is sometimes combined with a post-lithiation reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Ryu et al used a Couette-Taylor reactor to co-precipitate 0.3Li 2 MnO 3 • 0.7LiMn 0.60 Ni 0.25 Co 0.15 O 2 and found that 15 mol% excess lithium was necessary to form the desired layered compound. 19 Deng et al found that co-precipitated materials are very sensitive to lithium concentration, and lithium deficiency in the precursor solution can lead to the formation of spinel LiNi 0.5 Mn 1.5 O 4 upon lithiation, which was found to improve the rate capability of the materials upon cycling. 8,13 Since many synthesis methods are used to prepare the layered cathodes, different annealing conditions are applied to the as-synthesized powders, and this is sometimes combined with a post-lithiation reaction.…”
mentioning
confidence: 99%
“…8,13 Since many synthesis methods are used to prepare the layered cathodes, different annealing conditions are applied to the as-synthesized powders, and this is sometimes combined with a post-lithiation reaction. 6,8,19 Generally, as the annealing time and temperature increase the primary particles undergo coarsening. [20][21][22] However, it has also been observed that increasing the lithium content of the material promotes coarsening and thus, reduces surface area.…”
mentioning
confidence: 99%